(untitled) - Neustupnys, J. V. (Tokyo, 1978)
This book consists of the following: introduction on post structural , indeterminacy, variation, communicative competence, language problems linguistics of Japanese language.
Keywords: Japanese language,Linguistics; Social aspects,Research